Educating religious leaders to promote uptake of male circumcision in Tanzania: a cluster randomised trial. Issue 10074 (18th March 2017) - Downs, Jennifer A; Mwakisole, Agrey H; Chandika, Alphonce B; Lugoba, Shibide; Kassim, Rehema; Laizer, Evarist; Magambo, Kinanga A; Lee, Myung Hee; Kalluvya, Samuel E; Downs, David J; Fitzgerald, Daniel W
Summary: Background: Male circumcision is being widely deployed as an HIV prevention strategy in countries with high HIV incidence, but its uptake in sub-Saharan Africa has been below targets. We did a study to establish whether educating religious leaders about male circumcision would increase uptake in their village. Methods: In this cluster randomised trial in northwest Tanzania, eligible villages were paired by proximity (<60 km) and the time that a free male circumcision outreach campaign from the Tanzanian Ministry of Health became available in their village. All villages received the standard male circumcision outreach activities provided by the Ministry of Health. Within the village pairs, villages were randomly assigned by coin toss to receive either additional education for Christian church leaders on scientific, religious, and cultural aspects of male circumcision (intervention group), or standard outreach only (control group). Church leaders or their congregations were not masked to random assignment. The educational intervention consisted of a 1-day seminar co-taught by a Tanzanian pastor and a Tanzanian clinician who worked with the Ministry of Health, and meetings with the study team every 2 weeks thereafter, for the duration of the circumcision campaign. The primary outcome was the proportion of male individuals in a village who were circumcised during the campaign, using an intention-to-treat analysis that included all men in the village. This trial is registered withClinicalTrials.gov, numberNCT 02167776 . Findings: Between June 15, 2014, and Dec 10, 2015, we provided education for church leaders in eight intervention villages and compared the outcomes with those in eight control villages. In the intervention villages, 52·8% (30 889 of 58 536) of men were circumcised compared with 29·5% (25 484 of 86 492) of men in the eight control villages (odds ratio 3·2 [95% CI, 1·4–7·3]; p=0·006). Interpretation: Education of religious leaders had a substantial effect on uptake of male circumcision, and should be considered as part of male circumcision programmes in other sub-Saharan African countries. This study was conducted in one region in Tanzania; however, we believe that our intervention is generalisable. We equipped church leaders with knowledge and tools, and ultimately each leader established the most culturally-appropriate way to promote male circumcision. Therefore, we think that the process of working through religious leaders can serve as an innovative model to promote healthy behaviour, leading to HIV prevention and other clinically relevant outcomes, in a variety of settings. Funding: Bill & Melinda Gates Foundation, National Institutes of Health, and the Mulago Foundation.